Trois sonates pour le piano-forte : Oeuv. 10, No. 2 ... composées et dédiées à Madame la Comtesse de Browne par L. van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Hamburg; Jean Aug. Böhme; Germany, 2022)
Edition of the Piano Sonata no. 6 in F major, op.10, no. 2, published in an unnamed series by Jean Aug. Böhme in Hamburg. With decorative passé-partout title page that lists individual and set prices for all three sonatas of op. 10. Plate number 190-2. Paginated 16-27; also paginated 80-91.